The ministerialization of transitional justice - Lamont, Christopher (Human rights review, 2019)
In recent years, countries have begun to establish ministries of transitional justice (TJ) as part of political transitions from authoritarianism to democracy or from conflict to peace. This may reflect a broader historical trend in the administration of TJ, which has evolved from isolated offices within a particular ministry to ad hoc cross-ministry coordinating bodies to the establishment of dedicated ministries. The reasons for the establishment of specific ministries to pursue TJ, what we call ministerialization, have not attracted scholarly attention. This article explores the causes and likely consequences of this development. In particular, it applies international relations, comparative politics, and public policy theories to explain the phenomenon. Contrary to some TJ literature that is concerned about hegemonic transnational (largely Western) discourse, international actors have played little to no role in shaping how TJ is bureaucratically managed. Rather, based upon fieldwork in Solomon Islands and Tunisia, the article concludes that ministerialization has been the result of domestic policy entrepreneurship. For TJ ministries to become a norm, however, more transnational actors will need to be convinced of the benefits of such an institutional arrangement.